2002
DOI: 10.2165/00019053-200220050-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Splitting Tablets

Abstract: Tablet splitting appears to have limited usefulness as a cost-reduction strategy. Only a small proportion of products are suitable for splitting and have the potential for savings. There are also costs arising from splitting tablets in the pharmacy, or instructing patients to do so, and from wastage of product. There are also issues such as patient compliance and the risk of an incorrect dose being taken that should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Several studies studied the advantages of tablet splitting with regard to the health outcomes of patients, particularly within the geriatric and psychiatric communities. These advantages include dose adjustment [1], ease of swallowing and cost savings [2,3]. However, some studies revealed that splitting may result in the administration of an inaccurate dose, which can be of significant risk, especially if the split tablet formulation has a narrow therapeutic index [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies studied the advantages of tablet splitting with regard to the health outcomes of patients, particularly within the geriatric and psychiatric communities. These advantages include dose adjustment [1], ease of swallowing and cost savings [2,3]. However, some studies revealed that splitting may result in the administration of an inaccurate dose, which can be of significant risk, especially if the split tablet formulation has a narrow therapeutic index [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Further, effective instruction of the patients by the pharmacy is a prerequisite to minimise confusion and intake errors, especially when patients received information at the time of discharge that diverges from the finally dispensed medication. All processes may influence drug safety, take time and generate costs that may exceed the potential cost savings that physicians had advocated for splitting tablets [30]. For countries like Switzerland, where medication is dispensed in the original treatment pack, maximum savings from tablet splitting could theoreti-cally be obtained for products that have similar prices for each of the dosages.…”
Section: Discussionmentioning
confidence: 99%
“…Pills are frequently split to achieve dose flexibility, facilitate swallowing or reduce medication costs [2], [3]. However, the splitting of certain specific drugs is deemed unsafe, such as extended-release (ER) formulations and enteric-coated (EC) formulations because these specific kinds of formulations could be damaged by pill splitting, resulting in rapid absorption of the drug and a subsequent abrupt rise in blood concentration.…”
Section: Introductionmentioning
confidence: 99%